Sustainability assessment of Territorial Short Food Supply Chains versus Large‐Scale Food Distribution: The case of Colombia and Spain - Reina-Usuga, Liliana; Parra-López, Carlos; De Haro-Giménez, Tomás; Carmona-Torres, Carmen (Elsevier, 2023)
Assessing, designing and implementing more sustainable agri-food systems has become a high priority in scientific research and political agendas worldwide. The ongoing Russia-Ukraine conflict is highlighting the fragility of globalised food distribution systems, and there is a need to focus on alternatives. This manuscript assesses the sustainability of two largely opposing marketing alternatives, namely Territorial Short Food Supply Chains (TSFSCs) and Large-Scale Food Distribution (LSFD). Specifically, the cases of Bogota (Colombia) and Cordoba (Spain) are analysed, where the development of TSFSCs has very significant in recent years but which are of a very different nature. For this purpose, a multi-criteria model based on the Analytic Network Process (ANP) methodology has been developed, considering multiple economic, social and environmental criteria. The model has been evaluated by four interest groups. The results show that the social sub-criterion – distribution of added value – is highly prioritised, and that the TSFSCs are the most sustainable alternatives globally in both cities. In Bogota, direct sales (farmers market) are prioritised, whilst in Cordoba, chain with a local retail (specialised shops). The contribution of TSFSCs to ecosystem services, equity, territorial cohesion and the revitalisation of the economy is highlighted. By interest groups, civil society, academia and public administration prioritise TSFSCs. However, the market players in Cordoba prioritise LSFD with national product. The results indicate that TSFSCs have the potential to contribute to the consolidation of sustainable and resilient food systems.
Keywords: Alimentación; Ciudades - Servicios alimentarios; Alternative Food Networks; Territory; Sustainable food systems; Territorial resilience; Food supply chains; Food governance